Tom and I both think it's 8. (25 X .32)...in other words she gets 32 hits for every 100 times at bat, so it's 8 for every 32 times up. (But it took me till the end og my junior year to understand Algebra II. He's taking it now.)
I agree with the answer of 8, but its 8 for every 25 times at bat. To set it up as a proportion, use hits/times at bat = hits/times at bat So, make sure that both ratios are set up with a numerator of hits and a denominator of times at bat. Consistensy is the ket to setting up proportions! 32/100 = x/25 32(25) = 100x 800 = 100x 8 = x Anne could expect 8 hits if she had 25 times at bat with a batting average of 0.320.
I am living in the nightmare right now, I have this sheet of paper in front of me with a graph and a slope I am very scared
x + 3y ≤ 6 -x -x (subtract x from both sides) 3y ≤ -x + 6 (divide both sides by three) 3 3 (the dividing line on both sides did not show) y ≤ -x/3 + 6/3 y ≤ (-1/3)x + 2 slope = m = Δy/Δx = rise/run = -1/3 (write a negative in front of the 1 and a positive in front of the three) (you can equivalently write a positive in front of the 1 and a negative in front of the 3 – either way the overall fraction is negative) y intercept = 2 So, plot the point (0, 2) (this is on the y-axis, the up and down axis) From that go down in the negative y direction 1 and over in the positive x direction to the right 3. You will land at (3, 1). Do this again to get to (6, 0). Notice that the inequality was less than or equal to. Because of this draw a solid line through the points. If it were only less than or only greater than you would have drawn a dashed line. For shading: Find a point not on the line. Luckily (0, 0) is available. Substitute the x and y values from that ordered pair into the original inequality: x + 3y ≤ 6 0 + 3(0) ≤ 6 0 + 0 ≤ 6 0 ≤ 6 This is a true statement so shade from your line in the direction that included (0, 0). If it were false you would shade the opposite side.
Formatting can be frustrating sometimes on this board. Where you see -x -x One -x should be under the left hand side The other -x should be on the right hand side Where you see 3 3 One 3 should be under the left hand side The other 3 should be on the right hand side
Alternatively, the graph can also be determined by intercepts: x + 3y ≤ 6 For x-intercept, let y = 0 x + 3(0) = 6 x = 6 So plot (6, 0) For y-intercept, let x = 0 x + 3y =6 0 + 3y = 6 3y = 6 show that you divide both sides by 3 y = 6/3 y = 2 So plot (0, 2) Draw a solid line as explained before and shade as explained before
Monica, make sure to correct "The line would be y=-1X/2+2" To "The line would be y=-1X/3+2" Which is equivalent to the (-1/3)x + 2 in my post (we were helping at the same time)
For 4x - 8y = 8 First solve for y 4x-8y=8 subtract both sides by 4x -8y = -4x + 8 divide both sides by -8 y = (1/2)x - 1 (notice that -4 over -8 gives the fraction 1/2)(notice that 8 over -8 gives -1) so: Slope = 1/2 y intercept = -1 Will post more in a moment
Thank you so much for your help..This is all Greek to me but Kelton just said "oh yeah, that is how it is done" I am sure glad he knows what you all posted..I am in the dark and still very scared
For the 2nd problem: Change 4X-8Y=8 into the form of Y=mX+b This would be: -8Y = -4X + 8 Divide everything by -8, which gives you: Y - 1/2X - 1 The perpendicular line's slope is the negative reciprocal of the original line's slope. Original line's slope is 1/2. Perpendicular line's slope would be -2. Use the ordered pair given (1,2) to fill in for X and Y in the equation: 2 = -2(1) + b Now solve for b: 2= -2 + b; b = 4 Perpendicular line equation is Y = -2X + 4 Hope this makes sense.
Okay, in the last post I showed that the slope of the original line is 1/2. You need the slope of the new line which is perpendicular to the original line. To do this, you need the negative reciprocal of the original slope Original slope: 1/2 Slope of perpendicular: -(2/1) = -2 Now, you are given a point of (1, 2) Use the formula y – y1 = m(x – x1) We know that m = -2 We know that (x1, y1) = (1, 2) Substitute: y - 2 = -2(x - 1) Distribute y - 2 = -2x + 2 Add 2 to both sides (to isolate the y) y = -2x + 4
By the way, both Paula's method and mine are correct. Just go with whatever has been discussed in class.